PSIV-B-28 Late-Breaking: Performance and carcass quality of Nelore bull's progenies with contrasting traits for precocity, growth and muscularity. (5th December 2019) - Martins, Taiane S; Silva, Juliana; Mueller, Lenise; Amorim, Tamyres; Lobo, Annelise Aila G; Buarque, Vicente; Goméz, Juan; Cônsolo, Nara; Ferrinho, Adrielle D; Muñoz, Julian A; Moura, Gabriella; Gemelli, Jessica; et al.
Abstract: The goal of this study was to evaluate the performance and the carcass traits of Nelore cattle progenies from bulls selected by contrasting traits for precocity, growth and muscularity, through the Expected Progeny Difference (EPD). One hundred and five Nelore bulls (initial weight of 350kg±15kg) and 20 months of age were confined and fed with same diet (73% of concentrate). Thirty-two animals were selected to create the contrasting groups for precocity, growth and muscularity (16 animals assigned as a low EPD group - LEPD and 16 animals assigned as a high EPD group - HEPD), based on the EPD of their parents. The ribeye area and backfat thickness were performed by ultrasonography of 12–13 th rib fat thickness and longissimus muscle area (LMA), as well as rump fat thickness (RF) measurements. Animals were harvested after 100 days and during the deboning, meat cuts were weight for cutting yield. The animals selected for the HEPD group had greater average daily gain (P = 0.006), which can be explained by the higher feed intake (P = 0.006). However, there are no difference between groups for the final body weight (P = 0.254) and feed efficiency (P = 0.715). The LEPD group presented higher dressing percentage (P = 0.028). Although the groups evaluated did not presented difference in LMA (P = 0.329) and weight of longissimus muscle (P = 0.480), the weight of rump displayed heaviest in the HEPD (P = 0.037). There was no difference between groups for RF (P = 0.086). Nevertheless, backfat thickness was higher in HEPD group (P = 0.006). The present study indicates that Nelore cattle progenies, with parents displaying higher potential for precocity, growth, and muscularity, show greater backfat thickness and weightiest of rump than the other genetic backgrounds. Thanks to FAPESP for the scholarship (Grant # 2017/02349–1).